Mejoras en infraestructura y desempeño académico: evidencia de un experimento natural (2021)
This document evaluates the effect of the improvements in physical infrastructure conditions of schools in rural areas affected by La Niña in 2010-2011 in Colombia on the academic performance of students in standardized tests. Using administrative information of standardized tests (Saber 3ero, 5to, 9no and 11), the effect of improvements in conditions on academic performance is estimated employing the difference-in-differences method under an event study context. The results indicate that the intervention (the new infrastructure) presents a positive effect of 0.16 standard deviations in the performance of those students in the last grade of secondary school who benefited from the reconstructions, compared to the performance of those who are part of untreated schools. Likewise, there are not consistent results for the average of the global standardized scores of lower levels, especially from elementary students. These results are important in terms of the design and implementation of public policies since they show the need for reconstructions to be expedited, and that these be accompanied by improvements in pedagogical practices and the support of different actors such as parents.